Employee outcomes of talent identification and development - He, Zixin (My University, 2022)
Managing talents effectively has been regarded as one of the main solutions for human re-source challenges in current labor market. Based on the increasing mobility and globalization and the economic shift from product-based to knowledge-based businesses, more talented employees are needed, and organizations are updating their management strategies to be better confronted with talent challenges. Talent and talent management (TM) have become popular topics in human resource field for practitioners and literatures, especially from the 1990s. However, there is limited empirical research dealing with the ultimate questions of TM strategies – do TM strategies produce positive outcomes for employees and organizations? For organizations and employees alike, it is important to know if the “chosen ones” that are identified as “high potential” succeed or not in their subsequent career/roles. Therefore, it worth examining "Does TM produce the intended consequences?" More specifically, there are two sub-points to be explored: Are (1) talent identification and (2) talent development practices effective in supporting positive employee outcomes? In order to research the impact of TM strategy of the case company, data of 200 employees of a Finnish multinational (100 identified as talent, 100 not identified as talent in 2015) were selected to be studied. A hypothesis model is established to investigate the relationship between talent identification (being formally identified as talent, performance, and potential), talent development (joining development activities), and talent outcome (speed of promotion). To add more evidence for the research question and explore the opinions of TM managers towards the employee outcome, a supplementary interview was conducted. In terms of the findings, talent identification and development were found to have positive correlation to the career progress of employees. However, only being identified as talent can significantly lead to faster promotion in the company. Achieving higher performance, higher potential, or joining more (quantity of) development activities do not obviously result in faster promotion. The result suggests that exclusive TM is a proper and popular approach for selecting and developing a small number of employees to become future leaders. Therefore, identifying the correct and necessary talents are one of the most critical things in TM strategy, be-cause talents are allocated much more resources, their abilities and motivation may be improved, they may gain more opportunities, which can directly lead to positive outcomes such as promotion. The finding is supposed to be true for many other organizations. The topic also worth organizations and researchers to explore based on larger samples in the global scale. Because in real TM process, the assessment of employees’ performance and potential, the identification results, the process of development, and the employee outcomes may be influenced by objective conditions as well as subjective views and biases.
Keywords: human resource management; talent; development (active); organisations (systems); employees; career development; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business